Partnering with people living with dementia and care partners in technology research and design: Reflections and recommendations. (6th October 2022) - Liddle, Jacki; Worthy, Peter; Frost, Dennis; Taylor, Eileen; Taylor, Dubhglas
Abstract: Introduction: Occupational therapists may recommend and support technology use for facilitating independence, safety, wellbeing, and participation. There are high expectations for technology for people living with dementia. However, there is recognition that technologies will need to improve to deliver these expected benefits. People living with dementia have historically been excluded from direct involvement in research and design. A program of participatory research was undertaken to codesign technologies and technology research with people living with dementia and care partners. This work aims to capture the requirements, actions, and barriers experienced in forming these partnerships in technology research and design. Methods: A shared metareflection of experiences was conducted by members (5) of the research teams involved in three participatory research and technology design studies. The team comprising living experience experts, an occupational therapist, and interaction designer reflected on their experiences and derived recommendations. Key considerations for effective partnerships were drawn inductively by the authors from study experiences, materials, and reflexive discussion. Findings: Six core areas were identified. These were four action areas—(1) Agree on the value; (2) The time to start partnering is now; (3) Ask not assume; and (4) Push back on 'we always have'—(5) barriers and tensions, and (6) unexpected benefits. The reflections indicated that genuine partnerships and engagements were possible with living experience experts in research and design teams. These required resourcing and focussed actions to promote partnership. Despite some structural changes that encourage partnering, there are considerable barriers to this engagement; however, benefits beyond the expected ones can be realised. Conclusion: Genuine partnerships in technology research and design with living experience experts are possible and lead to benefits for the team, research outcomes, and technologies. Recommended actions could support expansion of effective partnerships with people living with dementia and care partners as well as other partnerships in research.